Metabolism-driven glycosylation represents therapeutic opportunities in interstitial lung diseases - Drzewicka, Katarzyna; Zasłona, Zbigniew (Frontiers in Immunology, 2024)
Metabolic changes are coupled with alteration in protein glycosylation. In this review, we will focus on macrophages that are pivotal in the pathogenesis of pulmonary fibrosis and sarcoidosis and thanks to their adaptable metabolism are an attractive therapeutic target. Examples presented in this review demonstrate that protein glycosylation regulate metabolism-driven immune responses in macrophages, with implications for fibrotic processes and granuloma formation. Targeting proteins that regulate glycosylation, such as fucosyltransferases, neuraminidase 1 and chitinase 1 could effectively block immunometabolic changes driving inflammation and fibrosis, providing novel avenues for therapeutic interventions.